Age and gender differences in coping style across various problems: Omani adolescents' perspective. Issue 2 (8th February 2013) - Al‐Bahrani, Muna; Aldhafri, Said; Alkharusi, Hussain; Kazem, Ali; Alzubiadi, Abdulqawi
ABSTRACT: This study examines adolescents' coping styles, with relation to their gender and age and level, of six types of problems. The participants were 1843 adolescents (51.7% female and 48.3% male) from the Sultanate of Oman with a mean age of 15.75. Two scales examining general adaptive and maladaptive coping styles and levels of school, economic, personal, health, family, and emotional problems were administered. The findings showed that adolescents' high levels of perceived problems were associated with higher levels of maladaptive coping styles than those with low levels of problems. Furthermore, female adolescents seem to use maladaptive coping styles (across all levels of the six types of problems) more than males. The use of adaptive and maladaptive coping styles increase with age.